2005
DOI: 10.1200/jco.2005.05.516
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Invasion Is Independently Associated With Overall Survival, Cause-Specific Survival, and Local and Distant Recurrence in Patients With Negative Lymph Nodes at Radical Cystectomy

Abstract: LVI is an independent predictor of recurrence and decreased cause-specific and overall survival in patients who undergo cystectomy for invasive bladder cancer and are node-negative. These patients represent a high risk group that may benefit from integrated therapy with cystectomy and perioperative systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
112
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 282 publications
(126 citation statements)
references
References 21 publications
13
112
0
1
Order By: Relevance
“…The impact of lymphovascular invasion on survival is important for several cancers; it is an independent risk factor for survival in colorectal, urothelial and breast cancers (Lotan et al 2005, Meguerditchian et al 2005, Rovera et al 2013. Data regarding the impact of lymphovascular invasion (LVI) on patient outcomes in PTC have been limited, based primarily on small, retrospective institutional studies (Kim et al 2006, Girardi et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of lymphovascular invasion on survival is important for several cancers; it is an independent risk factor for survival in colorectal, urothelial and breast cancers (Lotan et al 2005, Meguerditchian et al 2005, Rovera et al 2013. Data regarding the impact of lymphovascular invasion (LVI) on patient outcomes in PTC have been limited, based primarily on small, retrospective institutional studies (Kim et al 2006, Girardi et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, Quek et al 7 similarly noted that lymphovascular invasion was an independent prognostic variable in 702 patients with invasive cancer who underwent radical cystectomy without additional chemotherapy. Furthermore, Lotan et al 8 have claimed that lymphovascular invasion is an independent predictor of recurrence in patients with invasive cancer with negative lymph node involvement. In these studies no distinction was made between vascular invasion and lymphatic invasion.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that lymphovascular invasion is an independent predictor of recurrence and survival for invasive bladder cancer. 7,8 However, in other studies, lymphatic and vascular invasions are not a predictor of relapse, or survival. 5 In the current study, we reviewed and evaluated the clinical and pathological data and outcome in patients with bladder cancer, treated by radical cystectomy with lymphadenectomy at our institute, and found that lymphatic invasion was a prognostic factor for survival after surgery.…”
Section: Introductionmentioning
confidence: 96%
“…In UC of the bladder (UCB), LVI is a well-recognized risk factor for invasive tumor potential and possible presence of micrometastatic disease, which explains the close correlation between LVI and recurrence after radical cystectomy [29,30]. LVI is another risk factor that can be missed in ureteroscopic biopsies done for evaluation of UTUC prior to RNU.…”
Section: Discussionmentioning
confidence: 99%